Continuous vacuum nitrogen charging process and application thereof in food packaging bag

Through the combination of continuous vacuum nitrogen filling process and multi-layer structural packaging bags, the problems of food flavor loss and poor preservation effects in traditional packaging technology are solved, and efficient preservation and safe packaging of food are achieved.

CN119734879AActive Publication Date: 2025-04-01GUANGDONG INFINITY FOOD GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510091982.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-01
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Traditional vacuum packaging and nitrogen filling packaging technology have problems in food packaging such as food flavor loss, shape and appearance changes, limited freshness preservation effect, complex operation and safety risks.

Method used

Using continuous vacuum nitrogen filling process and homemade multi-layer structure packaging bags, packaging bags with high strength, high temperature resistance and good barrier properties are prepared through the instantaneous vacuum cavity degassing, instantaneous nitrogen filling, low vacuum instantaneous sealing and vacuum nitrogen filling sterilization steps.

Benefits of technology

It achieves efficient preservation of food, reduces the peroxide value of food, extends the shelf life, improves the pass rate of products, and provides safer and higher-quality food packaging solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251827800000141
    Figure BDA0005251827800000141
  • Figure BDA0005251827800000151
    Figure BDA0005251827800000151
Patent Text Reader

Abstract

The invention belongs to the technical field of packaging bags, and particularly relates to a continuous vacuum nitrogen charging process and application thereof in food packaging bags. The continuous vacuum nitrogen charging process comprises the following steps: S1, instantaneously degassing a vacuum cavity; s2, instantly charging nitrogen; s3, low-vacuum-degree instantaneous sealing is carried out; and S4, performing vacuum nitrogen charging sterilization. The self-made packaging bag can adapt to the continuous vacuum nitrogen filling process, is high in mechanical strength, good in toughness, resistant to high temperature, not prone to damage in the technological process and good in barrier property to oxygen and water vapor, the product quality guarantee period can be prolonged, the product peroxide value can be reduced, and therefore the product percent of pass is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of packaging bags, and in particular relates to a continuous vacuum nitrogen filling process and an application thereof in food packaging bags. Background Art

[0002] In recent years, with the significant improvement of people's living standards, consumers have a growing demand for convenient, healthy and delicious snack foods, which has put forward higher requirements for food packaging technology. Although traditional vacuum packaging technology can effectively isolate oxygen and extend the shelf life of food, it often causes serious loss of food flavor due to the high-intensity pressure during the sterilization process, and it is difficult to maintain the original shape and appearance of the raw materials, affecting the overall appearance of the product and consumer experience. In addition, vacuum packaging may also cause structural changes in food tissues, affecting the taste.

[0003] On the other hand, nitrogen-filled packaging technology reduces the oxygen content by replacing the air in the packaging bag, thereby slowing down the oxidation and deterioration process of food. However, this technology faces many challenges in practical applications, such as the difficulty in completely removing the air and oxygen molecules in the packaging bag, resulting in limited preservation effects; at the same time, it has high requirements for sterilization technology, complex operations, and safety risks, which limit its wide application in more food types. At present, nitrogen-filled packaging is mainly limited to puffed products such as potato chips and French fries, because it has little effect on shape retention and taste, but in other foods such as egg products that need to better maintain flavor and shape, the application effect is not ideal.

[0004] Therefore, the present invention proposes a continuous vacuum nitrogen filling process and prepares a packaging bag that can adapt to the continuous vacuum nitrogen filling process, providing a more efficient, safe and flexible packaging solution for food packaging bags. Summary of the invention

[0005] The purpose of the present invention is to provide a continuous vacuum nitrogen filling process and its application in food packaging bags. By making the packaging bags by themselves, the bags can be adapted to the continuous vacuum nitrogen filling process. The bags not only have high mechanical strength, good toughness and high temperature resistance, are not easily damaged during the process, but also have good barrier properties to oxygen and water vapor, can extend the shelf life of the products, reduce the peroxide value of the products, and thus improve the product qualification rate.

[0006] The continuous vacuum nitrogen filling process comprises the following steps:

[0007] S1. Instantaneous vacuum chamber degassing: Place the product to be packaged in the vacuum chamber and evacuate it to a vacuum degree below -0.09MPa;

[0008] S2. Instant nitrogen filling: Keep the vacuum chamber sealed, and instantaneously fill the vacuum chamber with pure nitrogen until the vacuum degree is 0.1MPa, and the nitrogen filling time is ≤5s;

[0009] S3, low vacuum instantaneous sealing: after filling with nitrogen, reduce the vacuum degree of the vacuum chamber to -0.02~-0.04MPa, and seal quickly before air and pollutants enter the packaging bag;

[0010] S4. Vacuum nitrogen sterilization: Sterilize the product while maintaining a vacuum nitrogen environment.

[0011] Preferably, the specific conditions for sealing are: sealing temperature of 150-200° C., sealing pressure of 0.3-0.5 MPa, and sealing time of 1-3 s.

[0012] Preferably, the specific conditions of the sterilization treatment are: a heating rate of 5-10°C / min, a sterilization temperature of 121-135°C, a pressure increase rate of 0.5-1.0 bar / min, and a sterilization time of 15-60 min.

[0013] The packaging bag is composed of bag bodies on both sides and a bottom film; the bag bodies on both sides have the same structure, which are, from inside to outside, the first support layer, the first barrier layer, and the second support layer; the bottom film has, from inside to outside, the third support layer, the second barrier layer, and the fourth support layer;

[0014] The first supporting layer and the third supporting layer are prepared using the same raw materials and the same preparation method.

[0015] Preferably, the raw material for preparing the first barrier layer includes AL; the raw material for preparing the second support layer includes PET; and the raw material for preparing the second barrier layer includes PA.

[0016] Preferably, the AL is an aluminum barrier film, which is commercially available and provided by Wuxi Color Printing Factory, and has a thickness of 13 μm.

[0017] Preferably, the intrinsic viscosity of the PET is 0.78-0.85 dl / g and the density is 1.2-1.6 g / cm 3 .

[0018] In some preferred embodiments, the PET is purchased from Changzhou China Resources, PET CR-8816.

[0019] Preferably, the tensile modulus of the PA is 1500-2000 MPa, and the notched impact strength at -30°C is 14-18 kJ / m2.

[0020] In some preferred embodiments, the PA is purchased from Suguan Technology, PA66 A3ST.

[0021] Preferably, the fourth supporting layer is OPET purchased from Colalist C#12.

[0022] The raw materials for preparing the first supporting layer include, by weight, 100 parts of polyethylene, 15-25 parts of polyamide, 10-20 parts of compatibilizer, 15-25 parts of inorganic modifier, 0.1-0.5 parts of lubricant, and 0.1-0.2 parts of antioxidant.

[0023] The packaging bag consists of a bag body on both sides and a bottom film; the bag body is made of PE-based material / AL / PET, and the bottom film is made of PE-based material / PA / OPET. The PE-based material of the bag body provides the necessary flexibility and strength, and is in direct contact with the contents to ensure safety and non-toxicity; while the middle AL layer plays its excellent oxygen barrier performance, effectively preventing oxygen from entering the packaging bag and extending the shelf life of the product. As the outer layer, the PET layer not only provides additional structural support and strength, but also forms a good bond with the AL layer to ensure the overall stability of the packaging bag. As for the bottom film, the PE-based material also provides the necessary strength and flexibility, and the PA layer further enhances the water vapor barrier performance and reduces the possibility of water vapor entering the packaging bag. The outermost OPET layer, after orientation treatment, has higher strength and rigidity, ensuring that the packaging bag has sufficient support at the bottom and is not easily deformed or damaged. This multi-layer structure design not only enables the packaging bag to show excellent adaptability and stability in the continuous vacuum nitrogen filling process, but also greatly improves the barrier performance to oxygen and water vapor, thereby effectively extending the shelf life of the product, reducing the peroxide value of the product, and significantly improving the product's pass rate, providing consumers with a safer and higher-quality product experience.

[0024] Preferably, the polyethylene includes linear low density polyethylene and metallocene polyethylene.

[0025] Preferably, the mass ratio of the linear low-density polyethylene to the metallocene polyethylene is (1-3):1; more preferably, it is 2:1.

[0026] Preferably, the linear low-density polyethylene has a melt index of 1-5 g / 10 min at 190°C and a density of 0.9-0.94 g / cm 3 , tear strength is 130-150kN / m.

[0027] In some preferred embodiments, the linear low-density polyethylene is purchased from Saudi Arabia SABI C, 318B.

[0028] Preferably, the metallocene polyethylene has a melt index of 0.5-2 g / 10 min at 190° C., a flexural modulus of 100-150 MPa, a tensile strength of 45-65 MPa, and an elongation at break of ≥600%.

[0029] In some preferred embodiments, the metallocene polyethylene is purchased from ExxonMobil, MPE 1012HJ.

[0030] By selecting specific linear low-density polyethylene and metallocene polyethylene, the mechanical properties of the first support layer can be significantly improved, thereby enhancing the strength and toughness of the entire packaging bag. This may be because linear low-density polyethylene has high strength, high toughness and good heat resistance, while metallocene polyethylene precisely controls the molecular structure through metallocene catalysts, showing high durability, tensile strength and excellent optical quality. The combination of the two not only achieves complementary performance, but also optimizes the molecular structure to form a more compact and orderly material system. In addition, the addition of metallocene polyethylene also improves the processing properties of the composite material, making the packaging bag easier to form and demold during the manufacturing process, and its addition can reduce the temperature required for heat sealing while maintaining a high heat sealing strength, which helps to reduce energy consumption and improve production efficiency while maintaining the integrity of the packaging bag. However, only polyethylene as the raw material of the first support layer has limited improvement in mechanical properties, and its heat resistance is relatively poor, which may affect the heat sealing strength of the vacuum bag.

[0031] The raw material of the polyamide is consistent with the raw material PA for preparing the second barrier layer.

[0032] By selecting polyamide and polyethylene for blending and modification, not only can the mechanical properties of the first support layer be significantly improved, but also its high temperature resistance can be improved, and it has a certain barrier effect, thereby improving the overall performance of the packaging bag. This may be because the blending of polyamide and polyethylene, on the one hand, promotes the formation of forces such as hydrogen bonds between molecules, helps to disperse stress, enhance the strength of the blend, and thus improve the strength of the packaging bag. On the other hand, it optimizes the entanglement degree and stability of the molecular chain, so that the blend exhibits higher strength and toughness when subjected to force, while improving heat resistance. In addition, PA has certain barrier properties, which, combined with the close arrangement of PE molecular chains, effectively prevents the penetration of gases or chemicals and improves the barrier effect of the vacuum bag. However, the compatibility between PA and PE is poor, which affects the mechanical properties of the packaging bag. In addition, the affinity between the polyethylene-based material of the support layer and the first barrier layer and the second barrier layer material is also poor, and long-term use may cause stratification, affecting the various properties of the vacuum bag.

[0033] Preferably, the compatibilizer includes one or more of maleic anhydride grafted EVA and maleic anhydride grafted LDPE; further preferably, maleic anhydride grafted EVA and maleic anhydride grafted LDPE.

[0034] Preferably, the mass ratio of the maleic anhydride grafted EVA to the maleic anhydride grafted LDPE is 1:(2-4); more preferably, it is 1:3.

[0035] Preferably, the maleic anhydride grafted EVA has a melt index of 2-4 g / 10 min at 190° C., a maleic anhydride grafting rate of 1%-1.2%, and a VA content of 25%-30%.

[0036] Preferably, the maleic anhydride grafted LDPE has a melt index of 5-7 g / 10 min at 190° C., and a maleic anhydride grafting rate of 1%-1.3%.

[0037] In some preferred embodiments, the maleic anhydride grafted EVA and maleic anhydride grafted LDPE are purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.

[0038] By selecting a specific compatibilizer, not only can the compatibility between polyethylene and polyamide be improved, but also the affinity between the barrier layer (AL or PA) and the polyethylene-based material of the support layer can be improved, avoiding interlayer separation caused by use under high temperature and high pressure, which affects the heat seal strength. This may be because the two compatibilizers work synergistically, not only reducing the polarity difference between PE and PA, but also promoting the chemical bonding between them. Thermodynamically, as surfactants, they reduce the interfacial tension, increase the thickness of the interfacial layer, and promote the reduction of the size of the dispersed particles, thereby forming a thermodynamically stable phase structure with macroscopic uniformity and microscopic phase separation. In addition, the maleic anhydride grafted compatibilizer can also promote the interpenetration and interweaving between the PE and PA molecular chains, forming a fuzzy interface, and enhancing the adhesion between the barrier layer and the support layer. At the same time, the hydrogen bonding that may be formed between the anhydride group and the amide group further enhances the interaction between them. These synergistic mechanisms jointly improve the morphological stability of the composite material, making it difficult for interlayer separation to occur between the barrier layer and the support layer when used under high temperature and high pressure, thereby ensuring the stability of the heat seal strength.

[0039] Preferably, the inorganic modifier is modified montmorillonite.

[0040] By selecting montmorillonite as an inorganic modifier, the mechanical properties, dimensional stability and high temperature resistance of the first support layer can be significantly improved, thereby enhancing the overall performance of the packaging bag. This may be because montmorillonite, as a layered silicate mineral, has excellent adsorption properties and ion exchange capacity. It can be evenly dispersed between PE molecular chains to form effective physical cross-linking points, thereby improving the mechanical properties of the material such as tensile strength, bending strength and impact strength. At the same time, the layered structure of montmorillonite can also effectively prevent the thermal motion of PE molecular chains and improve the thermal stability and dimensional stability of the material. However, montmorillonite has poor dispersibility in PE-based materials and is easy to agglomerate, which affects its modification effect on PE-based materials.

[0041] The preparation method of the modified montmorillonite comprises the following steps:

[0042] A1. After the montmorillonite is crushed through a 200-400 mesh sieve, it is ultrasonically dispersed in an 80wt% ethanol aqueous solution for 1-3h, and a silane coupling agent is added to adjust the pH value of the system to 8-9. After reacting at 60-80°C for 2-4h, it is cooled to room temperature, filtered and separated, and then washed with deionized water until neutral, and vacuum dried at 60-70°C to obtain silane coupling agent modified montmorillonite;

[0043] A2. Mix the silane coupling agent modified montmorillonite with water, stir and heat to 80-90°C, add long-chain fatty acid, react for 8-10 hours, filter and separate, wash with deionized water to neutrality, and vacuum dry at 60-70°C to obtain modified montmorillonite.

[0044] Preferably, the montmorillonite is sodium-montmorillonite, has an ion exchange capacity of 140-150 meq / 100 g, and an aspect ratio of 200-400.

[0045] In some preferred embodiments, the montmorillonite is purchased from Jiangsu Xianfeng Nanomaterial Technology.

[0046] Preferably, the mass ratio of the montmorillonite to the 80 wt % ethanol aqueous solution is 1:(10-20).

[0047] Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0048] Preferably, the mass ratio of the γ-aminopropyltriethoxysilane to the γ-methacryloxypropyltrimethoxysilane is 1:(0.5-2); more preferably, it is 1:1.

[0049] Preferably, the amount of the silane coupling agent added is 5% to 10% of the mass of the montmorillonite.

[0050] Preferably, the mass ratio of the silane coupling agent modified montmorillonite to water is 1:(40-50).

[0051] Preferably, the long-chain fatty acid includes one or more of oleic acid, linolenic acid and palmitic acid; further preferably, linolenic acid.

[0052] Preferably, the addition amount of the long-chain fatty acid is 3-5 times the mass of the silane coupling agent-modified montmorillonite.

[0053] By first grafting silane coupling agent on the surface of montmorillonite for primary modification, and then using linolenic acid for secondary modification, the dispersibility and compatibility of montmorillonite in PE-based materials can be improved, thereby further improving the performance of packaging bags. This may be because the silane coupling agent can form covalent bonds with the hydroxyl groups on the surface of montmorillonite through hydrolysis and condensation reactions, thereby firmly grafting onto the montmorillonite, which not only changes the hydrophilicity of montmorillonite, but also increases its interlayer spacing, providing favorable conditions for further intercalation of polymer chains. The introduction of linolenic acid further modifies the surface of the modified montmorillonite and enhances the interaction between it and the PE molecules. The functional groups in the linolenic acid molecules have a strong interaction with the surface of the montmorillonite modified by the silane coupling agent. This interaction not only improves the binding force between the two, but also further improves the compatibility of montmorillonite with PE. Through this double modification, the dispersibility of montmorillonite in the PE matrix is ​​significantly improved, and the agglomeration phenomenon is effectively suppressed. Moreover, the silane coupling agent and linolenic acid selected in the present application are both non-toxic and harmless, and are suitable for application fields with high safety requirements such as food packaging bags.

[0054] Preferably, the lubricant is one or more of paraffin, calcium stearate, barium stearate, ethylene bis stearic acid amide, and pentaerythritol stearate; more preferably, pentaerythritol stearate and ethylene bis stearic acid amide.

[0055] Preferably, the mass ratio of pentaerythritol stearate to ethylene bisstearic acid amide is 1:(1-3), more preferably, 1:2.

[0056] Preferably, the antioxidant includes one or more of antioxidant 1010, antioxidant 168, and antioxidant 1076; more preferably, antioxidant 1010 and antioxidant 168.

[0057] Preferably, the mass ratio of the antioxidant 1010 to the antioxidant 168 is (1-2):1; more preferably, it is 3:2.

[0058] The method for preparing the packaging bag comprises the following steps:

[0059] B1. Preparation of bag body: adding the raw material of the first supporting layer into a film blowing machine, and blowing the film at 190-220°C; adding the raw material of the second supporting layer into a film blowing machine, and blowing the film at 180-230°C; compounding the first supporting layer, the first barrier layer and the second supporting layer by dry compounding technology to obtain;

[0060] B2. Preparation of base film: Add the raw materials of the third support layer, the second barrier layer and the fourth support layer into a multi-layer co-extrusion film blowing machine according to the formula ratio, set the temperature of the third support layer to 190-220°C, the temperature of the second barrier layer to 240-260°C, the temperature of the third barrier layer to 250-280°C, adjust the screw speed to 30-60rpm, the traction speed to 5-15m / nib, the winding tension to 0.5-1.0N / mm2, and cool and shape to obtain the base film;

[0061] B3. Compound the two layers of bag body and the bottom film to obtain a packaging bag.

[0062] Preferably, the thickness of the first supporting layer is 50-100 μm; the thickness of the first barrier layer is 13 μm; and the thickness of the second supporting layer is 12-20 μm.

[0063] For the specific operation process of the dry composite technology, please refer to the paper "Research on Composite Process of Tropical Aluminum Composite Materials" published by Liao Shuai.

[0064] Preferably, the thickness of the third supporting layer is 50-70 μm; the thickness of the second barrier layer is 15-25 μm; and the thickness of the fourth supporting layer is 12-20 μm.

[0065] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0066] 1. The present invention provides a continuous vacuum nitrogen filling process. By making a self-made packaging bag, it can adapt to the continuous vacuum nitrogen filling process. It not only has high mechanical strength, good toughness and high temperature resistance, is not easy to be damaged in the process flow, but also has good barrier properties to oxygen and water vapor, can extend the shelf life of the product, reduce the peroxide value of the product, and thus improve the product qualification rate.

[0067] 2. The present invention can significantly improve the mechanical properties of the first supporting layer by selecting specific linear low-density polyethylene and metallocene polyethylene, thereby enhancing the strength and toughness of the entire packaging bag.

[0068] 3. The present invention adopts polyamide and polyethylene for blending and modification, which can not only significantly improve the mechanical properties of the first supporting layer, but also improve its high temperature resistance and have a certain barrier effect, thereby improving the overall performance of the packaging bag.

[0069] 4. The present invention can improve the compatibility between polyethylene and polyamide by selecting a specific compatibilizer, and can also improve the affinity between the barrier layer (AL or PA) and the polyethylene-based material of the support layer, thereby avoiding interlayer separation caused by use under high temperature and high pressure, which affects the heat sealing strength.

[0070] 5. The present invention uses montmorillonite as an inorganic modifier, which can significantly improve the mechanical properties, dimensional stability and high temperature resistance of the first support layer, thereby enhancing the overall performance of the packaging bag; and firstly grafting a silane coupling agent on the surface of the montmorillonite for primary modification, and then using linolenic acid for secondary modification, which can improve the dispersibility and compatibility of montmorillonite in PE-based materials, thereby further improving the performance of the packaging bag. DETAILED DESCRIPTION

[0071] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0072] The raw materials used in the present invention are all commercially available, specifically:

[0073] AL is an aluminum barrier film, commercially available, provided by Wuxi Color Printing Factory, with a thickness of 13 μm.

[0074] PET, intrinsic viscosity is 0.78-0.85dl / g, density is 1.2-1.6g / cm 3 , purchased from Changzhou China Resources, PET CR-8816.

[0075] PA, with a tensile modulus of 1500-2000 MPa and a notched impact strength of 14-18 kJ / m2 at -30°C, was purchased from Suguan Technology, PA66 A3ST.

[0076] OPET, purchased from Colarist C#12.

[0077] The melt index of linear low-density polyethylene at 190°C is 1-5g / 10min, and the density is 0.9-0.94g / cm 3 , tear strength is 130-150kN / m, purchased from Saudi SAB IC, 318B.

[0078] The metallocene polyethylene has a melt index of 0.5-2 g / 10 min at 190° C., a flexural modulus of 100-150 MPa, a tensile strength of 45-65 MPa, and an elongation at break of ≥600%, and is purchased from ExxonMobil, MPE 1012HJ.

[0079] The melt index of maleic anhydride grafted EVA at 190°C is 2-4g / 10min, the maleic anhydride grafting rate is 1%-1.2%, and the VA content is 25%-30%; the melt index of maleic anhydride grafted LDPE at 190°C is 5-7g / 10min, and the maleic anhydride grafting rate is 1%-1.3%; purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.

[0080] The montmorillonite is sodium montmorillonite with an ion exchange capacity of 140-150 meq / 100 g and an aspect ratio of 200-400, purchased from Jiangsu Xianfeng Nanomaterial Technology.

[0081] Example 1

[0082] This embodiment provides a continuous vacuum nitrogen filling process, the steps are:

[0083] S1. Instantaneous vacuum chamber degassing: Place the product to be packaged in the vacuum chamber and evacuate to a vacuum degree of -0.08MPa;

[0084] S2, instantaneous nitrogen filling: keep the vacuum chamber sealed, and instantaneously fill the vacuum chamber with pure nitrogen until the vacuum degree is 0.1MPa, and the nitrogen filling time is 5s;

[0085] S3, low vacuum instantaneous sealing: after filling with nitrogen, reduce the vacuum degree of the vacuum chamber to -0.03MPa, and seal quickly before air and pollutants enter the packaging bag;

[0086] S4. Vacuum nitrogen sterilization: Sterilize the product while maintaining a vacuum nitrogen environment.

[0087] The specific sealing conditions are: sealing temperature is 180° C., sealing pressure is 0.4 MPa, and sealing time is 2 s.

[0088] The specific conditions of the sterilization treatment are: a heating rate of 8°C / min, a sterilization temperature of 128°C, a pressure increase rate of 0.8 bar / min, and a sterilization time of 40 min.

[0089] The packaging bag is composed of bag bodies on both sides and a bottom film; the bag bodies on both sides have the same structure, which are, from inside to outside, the first support layer, the first barrier layer, and the second support layer; the bottom film has, from inside to outside, the third support layer, the second barrier layer, and the fourth support layer;

[0090] The first supporting layer and the third supporting layer are prepared using the same raw materials and the same preparation method.

[0091] The first barrier layer is made of AL; the second support layer is made of PET; the second barrier layer is made of PA; and the fourth support layer is made of OPET.

[0092] The raw materials for preparing the first supporting layer are, by weight, 100 parts of polyethylene, 20 parts of polyamide, 15 parts of compatibilizer, 20 parts of inorganic modifier, 0.3 parts of lubricant, and 0.15 parts of antioxidant.

[0093] The polyethylene is linear low-density polyethylene and metallocene polyethylene, and the mass ratio is 2:1.

[0094] The raw material of the polyamide is consistent with the raw material PA for preparing the second barrier layer.

[0095] The compatibilizer is maleic anhydride grafted EVA and maleic anhydride grafted LDPE, with a mass ratio of 1:3.

[0096] The inorganic modifier is modified montmorillonite.

[0097] The preparation method of the modified montmorillonite comprises the following steps:

[0098] A1. After the montmorillonite is crushed and passed through a 300-mesh sieve, it is ultrasonically dispersed in an 80 wt% ethanol aqueous solution for 2 h, and a silane coupling agent is added to adjust the pH value of the system to 9. After reacting at 70° C. for 3 h, it is cooled to room temperature, filtered and separated, and washed with deionized water until neutral, and vacuum dried at 65° C. to obtain silane coupling agent-modified montmorillonite;

[0099] A2. Mix the silane coupling agent-modified montmorillonite with water, stir and heat to 85°C, add long-chain fatty acids, react for 9 hours, filter and separate, wash with deionized water to neutrality, and vacuum dry at 65°C to obtain modified montmorillonite.

[0100] The mass ratio of the montmorillonite to the 80wt% ethanol aqueous solution is 1:15.

[0101] The silane coupling agent is γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane, and the mass ratio is 1:1.

[0102] The added amount of the silane coupling agent is 8% of the mass of the montmorillonite.

[0103] In A2, the mass ratio of the silane coupling agent modified montmorillonite to water is 1:50.

[0104] The long-chain fatty acid is linolenic acid, and the added amount is 4 times the mass of the silane coupling agent-modified montmorillonite.

[0105] The lubricant is pentaerythritol stearate and ethylene bis stearamide, with a mass ratio of 1:2.

[0106] The antioxidants are antioxidant 1010 and antioxidant 168, with a mass ratio of 3:2.

[0107] The preparation method of the packaging bag comprises the following steps:

[0108] B1. Preparation of bag body: adding the raw material of the first supporting layer into a film blowing machine, and blowing the film at 210°C; adding the raw material of the second supporting layer into a film blowing machine, and blowing the film at 220°C; compounding the first supporting layer, the first barrier layer and the second supporting layer by dry compounding technology to obtain;

[0109] B2. Preparation of base film: Add the raw materials of the third support layer, the second barrier layer and the fourth support layer into a multi-layer co-extrusion film blowing machine according to the formula ratio, set the temperature of the third support layer to 205°C, the temperature of the second barrier layer to 250°C, and the temperature of the third barrier layer to 270°C, adjust the screw speed to 50rpm, the traction speed to 10m / nib, and the winding tension to 0.8N / mm2, and obtain the film after cooling and finalization;

[0110] B3. Compound the two layers of bag body and the bottom film to obtain a packaging bag.

[0111] The thickness of the first supporting layer is 70 μm; the thickness of the first barrier layer is 13 μm; and the thickness of the second supporting layer is 16 μm.

[0112] For the specific operation process of the dry composite technology, please refer to the paper "Research on Composite Process of Tropical Aluminum Composite Materials" published by Liao Shuai.

[0113] The thickness of the third supporting layer is 60 μm; the thickness of the second barrier layer is 20 μm; and the thickness of the fourth supporting layer is 16 μm.

[0114] Example 2

[0115] The difference between this embodiment and embodiment 1 is that the raw materials for preparing the first supporting layer are, by weight, 100 parts of polyethylene, 18 parts of polyamide, 13 parts of compatibilizer, 22 parts of inorganic modifier, 0.3 parts of lubricant, and 0.15 parts of antioxidant.

[0116] Comparative Example 1

[0117] The difference between this comparative example and Example 1 is that the polyethylene is linear low-density polyethylene.

[0118] Comparative Example 2

[0119] The difference between this comparative example and Example 1 is that the raw materials for preparing the first supporting layer, by weight, are 100 parts of polyethylene, 10 parts of polyamide, 15 parts of compatibilizer, 20 parts of inorganic modifier, 0.3 parts of lubricant, and 0.15 parts of antioxidant.

[0120] Comparative Example 3

[0121] The difference between this comparative example and Example 1 is that the raw materials for preparing the first supporting layer, by weight, are 100 parts of polyethylene, 20 parts of polyamide, 5 parts of compatibilizer, 20 parts of inorganic modifier, 0.3 parts of lubricant, and 0.15 parts of antioxidant.

[0122] Comparative Example 4

[0123] The difference between this comparative example and Example 1 is that the compatibilizer is maleic anhydride grafted EVA.

[0124] Comparative Example 5

[0125] The difference between this comparative example and Example 1 is that the inorganic modifier is montmorillonite.

[0126] Comparative Example 6

[0127] The difference between this comparative example and Example 1 is that the preparation method of the modified montmorillonite comprises the following steps: the montmorillonite is crushed through a 300-mesh sieve and then ultrasonically dispersed in an 80wt% ethanol aqueous solution for 2 hours, a silane coupling agent is added, the pH value of the system is adjusted to 9, the reaction is carried out at 70°C for 3 hours, the reaction is cooled to room temperature, the mixture is filtered and separated, and then washed with deionized water until neutral, and vacuum dried at 65°C.

[0128] Performance Testing

[0129] Refer to GB / T 1040.3-2006 to test the tensile strength and elongation at break, the units are MPa and % respectively; refer to GB / T 19789-2021 to test the oxygen permeability coefficient of the material, the unit is cm 3 m / (m 2 ·d·Pa); refer to GB 1037-70 test material water vapor transmission coefficient, unit is g·m / (m 2 ·d·Pa); refer to QB / T 2358-1998 to test the heat seal strength of materials, the unit is MPa; refer to GB / T 21302-2007 to test the heat resistance of packaging bags at 150°C, no deformation, no delamination, no cracking is qualified. The results are shown in Table 1.

[0130] Table 1 Measurement results

[0131]

[0132]

[0133] According to statistics, the packaging bags prepared by Examples 1 to 2 of the present invention not only have high mechanical strength, good toughness and high temperature resistance, are not easy to break in the process flow, but also have good barrier properties to oxygen and water vapor, can extend the product shelf life, reduce the product peroxide value, and thus improve the product qualification rate. Comparative Example 1 does not add metallocene polyethylene, Comparative Example 2 has a small amount of polyamide added, Comparative Example 3 has a small amount of compatibilizer added, Comparative Example 4 does not add maleic anhydride grafted LDPE, Comparative Example 5 does not modify montmorillonite, and Comparative Example 6 does not perform secondary modification on montmorillonite. The tensile strength, elongation at break, and heat sealing strength of the prepared packaging bags are all low, the oxygen permeability coefficient and water vapor permeability coefficient are high, and the heat resistance is poor. Therefore, the packaging bags prepared by the raw materials and methods described in this application not only have high mechanical strength, good toughness and high temperature resistance, are not easy to break in the vacuum nitrogen filling process described in this application, but also have good barrier properties to oxygen and water vapor, can extend the product shelf life, reduce the product peroxide value, and thus improve the product qualification rate.

[0134] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A continuous vacuum nitrogen filling process, characterized in that: The following steps are involved: S1. Instantaneous vacuum chamber degassing: Place the product to be packaged in the vacuum chamber and evacuate it to a vacuum degree below -0.09MPa; S2. Instant nitrogen filling: Keep the vacuum chamber sealed, and instantaneously fill the vacuum chamber with pure nitrogen until the vacuum degree is 0.1MPa, and the nitrogen filling time is ≤5s; S3, low vacuum instantaneous sealing: after filling with nitrogen, reduce the vacuum degree of the vacuum chamber to -0.02~-0.04MPa, and seal quickly before air and pollutants enter the packaging bag; S4, Vacuum nitrogen filling sterilization: Sterilize the product while maintaining the vacuum nitrogen filling environment; The packaging bag is composed of bag bodies on both sides and a bottom film; the bag bodies on both sides have the same structure, which are, from inside to outside, the first support layer, the first barrier layer, and the second support layer; the bottom film has, from inside to outside, the third support layer, the second barrier layer, and the fourth support layer; The first supporting layer and the third supporting layer are prepared using the same raw materials and methods; the second supporting layer is prepared using the same raw materials as PET; The raw material for preparing the first barrier layer includes AL; the raw material for preparing the second barrier layer includes PA; The raw materials for preparing the first supporting layer include, by weight, 100 parts of polyethylene, 15-25 parts of polyamide, 10-20 parts of compatibilizer, 15-25 parts of inorganic modifier, 0.1-0.5 parts of lubricant, and 0.1-0.2 parts of antioxidant; the polyethylene includes linear low-density polyethylene and metallocene polyethylene.

2. The continuous vacuum nitrogen filling process according to claim 1, characterized in that: The specific conditions of the sealing are: the sealing temperature is 150-200° C., the sealing pressure is 0.3-0.5 MPa, and the sealing time is 1-3 s.

3. The continuous vacuum nitrogen filling process according to claim 1, characterized in that: The specific conditions of the sterilization treatment are: a heating rate of 5-10°C / min, a sterilization temperature of 121-135°C, a pressure increase rate of 0.5-1.0 bar / min, and a sterilization time of 15-60 min.

4. The continuous vacuum nitrogen filling process according to claim 1, characterized in that: The linear low-density polyethylene has a melt index of 1-5 g / 10 min at 190° C. and a density of 0.9-0.94 g / cm 3 , tear strength is 130-150kN / m.

5. The continuous vacuum nitrogen filling process according to claim 1, characterized in that: The metallocene polyethylene has a melt index of 0.5-2 g / 10 min at 190° C., a flexural modulus of 100-150 MPa, a tensile strength of 45-65 MPa, and an elongation at break of ≥600%.

6. The continuous vacuum nitrogen filling process according to claim 1, characterized in that: The fourth supporting layer is OPET.

7. The continuous vacuum nitrogen filling process according to claim 1, characterized in that: The compatibilizer includes one or more of maleic anhydride grafted EVA and maleic anhydride grafted LDPE.

8. The continuous vacuum nitrogen filling process according to claim 1, characterized in that: The inorganic modifier is modified montmorillonite.

9. The continuous vacuum nitrogen filling process according to claim 8, characterized in that: The preparation method of the modified montmorillonite comprises the following steps: A1. After the montmorillonite is crushed through a 200-400 mesh sieve, it is ultrasonically dispersed in an 80wt% ethanol aqueous solution for 1-3h, and a silane coupling agent is added to adjust the pH value of the system to 8-9. After reacting at 60-80°C for 2-4h, it is cooled to room temperature, filtered and separated, and then washed with deionized water until neutral, and vacuum dried at 60-70°C to obtain silane coupling agent modified montmorillonite; A2. Mix the silane coupling agent modified montmorillonite with water, stir and heat to 80-90°C, add long-chain fatty acid, react for 8-10 hours, filter and separate, wash with deionized water to neutrality, and vacuum dry at 60-70°C to obtain modified montmorillonite.

10. Use of the continuous vacuum nitrogen filling process according to any one of claims 1 to 9 in food packaging bags.

Citation Information

Patent Citations

  • Full-degradable cushion packaging bag and preparation method thereof

    CN107556711A

  • Small-package modified atmosphere preservation method for rice and product

    CN118289273A

  • Ultrahigh-barrier homogenized composite packaging film and preparation process thereof

    CN119141990A

  • Nitrogen packaging bag

    CN202807328U

  • Packaging bag

    JP2023111750A